Gamma and beta radiolysis of tri-iso-amyl phosphate: Degradation of tri-iso-amyl phosphate and formation of di-iso-amyl phosphoric acid. (October 2022) - Li, Fengzhen; Qin, Yilin; Liao, Wei; Li, Feize; Lan, Tu; Ding, Songdong; Liao, Jiali; Yang, Jijun; Yang, Yuanyou; Feng, Wen; Liu, Ning
Abstract: Tri-iso-amyl phosphate (TiAP) is considered a potential alternative solvent to tri-butyl phosphate (TBP) for aqueous reprocessing of molten salt reactors and fast reactor fuels. This study explored the γ and β radiolysis of TiAP under various conditions through the analysis of the radiolytic concentration changes of TiAP and the yields of di-iso-amyl phosphoric acid (DiAP) using gas chromatography. The results indicated that the effects of dose, diluent, and nitric acid on the radiolysis of TiAP under γ-and β-irradiations showed a similar regularity. The degradation rate of TiAP followed a first-order reaction, and the paraffinic diluent was able to sensitize TiAP. Although the presence of nitric acid promoted the radiolysis of TiAP and the formation of DiAP in a neat TiAP system, it did not lead to significant changes in the 36%TiAP/n-DD system, implying that nitric acid is involved in an intricate process. Furthermore, based on these results, possible degradation mechanisms of TiAP were described. Highlights: The γ and β radiolysis of TiAP under various conditions were explored. A method for simultaneous determination of TiAP and DiAP was established. The effect of diluent and nitric acid on the degradation of TiAP and formation of DiAP was provided.